The Regional Consequences of Regime Change in Iraq: in A CIA Report - Prof. Dr. Ali Khairi Matroud (Journal of College of Education, 2025)
This research examines a secret report prepared by the Central Intelligence Agency (CIA) prior to the 2003 invasion of Iraq, based on a group of experts and specialized locals. It identifies and evaluates the nature, type, and extent of the consequences and repercussions that will result from the invasion and the overthrow of the Iraqi regime, whether those consequences are internal to Iraq or regionally and globally, especially those related to the United States of America and its position in the world and the region.
Keywords: Iraq; Islamic movements; terrorism; public opinion; conflict